Outcome Evaluation of Eyelid Laceration Surgery in Kariadi General Hospital Semarang: Oral Presentation - Observational Study - Resident - NIZAR ARIF LAZUARDI; TRILAKSANA NUGROHO (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : Eyelid laceration are common in cases of trauma involving the eye. This study will discuss cases of eyelid lacerations, procedures, and the follow-up of patients who underwent surgery at Kariadi General Hospital Semarang. Methods : This study used an observational analytic design and was conducted retrospectively. All patients who underwent eyelid surgery April 2019 to January 2023. Age, gender, laceration location, mechanism of trauma, canalicular involvement, and surgery were recorded, subjective complaints and patient complications after surgery. Results : Of the 76 patients (94 eyelid lacerations) included in the study, men exhibited a greater vulnerability (56,75%) and mostly aged around 16-<50 years (43, 57%). In terms of the laceration location, it occurred in right lower (39,36%), right upper (35,10%), left lower (13,82%), and left upper (11,70%) eyelids. Blunt trauma (83,78%) was the main mechanism, with motor vehicle accidents leading (40,54%). Canalicular involvement was present in 35 cases (47,29%). All patients underwent surgery, with eyelid repair to all of the patient following by recanalization (39,18%). The most common complaint of patients after surgery in the first week of control was pain (47,29%) followed by a feeling of lump (13,51%). A total of 25 patients (33,78%) stated that they had no complaints. Conclusion : Eyelid lacerations mainly involve young adult people, right lower eyelid. Blunt trauma, particularly motor vehicle accidents, is the main cause. Most of the patients had no complaints in the1 week postoperative control, and they increased in subsequent controls.